Penerapan Ragam Hias Ni’o afi afi dengan Teknik Circle and Triangles pada Gaun Pengantin - Rut Dhea Epyravita; Yuhri Inang Prihatina (BAJU: Journal of Fashion and Textile Design Unesa, 2022)
The purpose of this research is to determine the process of application and the result of the development of ni'o afi-afi ornaments as wedding dress ornaments. Inspired by the folklore of North Sumatra "Samaehowu Foriwu", which means nobility. Ni'o afi afi was developed into a manipulating fabric circle and triangle plus sequin embroidery to add a luxurious and beautiful impression. The method used is Double Diamond, which consists of 4 stages, namely discover, define, develop and deliver. To get a response to the results of the application of the ni'o afi-afi decoration, a questionnaire was used to see the suitability of the design of the source of inspiration, the accuracy of the process according to the source of inspiration to the suitability of the result of the design and the source of inspiration. The results obtained from the aspect of design, process and finished products received a very good response. In the design aspect, both the color and the silhouette match the source of ni'o afi afi's inspiration. In the aspect of the process of realizing manipulating fabric circles and triangles with the addition of sequin embroidery, a very good response was obtained. The finished results obtained in terms of suitability of results and usability also received a very good response, namely the application of the ni'o afi afi decoration with the circle and triangles technique on the wedding dress as a whole very much in accordance with the source of inspiration.